Increasing Community Knowledge About Preventing Stunting and Making Additional Food in Cikurubuk Village, Buahdua District 2024 - Mona Yulianti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Stunting is a problem of nutrition and growth and development in children in Indonesia that has not been resolved optimally. Cikurubuk Village is the 2023 stunting locus in Buahdua District with an incidence rate of 0.8%. The implementation of this community service aims to increase community knowledge about stunting and increase community knowledge about fulfilling nutritious supplementary food as an effort to prevent stunting. This community service activity was carried out in January 2024. The focus of this community service activity is increasing public awareness about stunting and efforts to prevent it through providing additional food for toddlers and children. The community carried out a pre-test before providing counseling with the aim of getting a picture of community knowledge about stunting and providing additional food. Counseling is carried out offline, including counseling about stunting and efforts to prevent stunting and PMT as well as training in making additional food made from local and nutritious ingredients for toddlers and children. The community took the post test again after being given the counseling with the aim of finding out a picture of the community's knowledge after being given the counseling. As a result, after being given counseling, public knowledge about stunting and complementary foods increased. This activity went smoothly and the community was very enthusiastic about listening to the outreach. Participants in this counseling were cadre mothers and teenagers totaling 50 people.